2013
DOI: 10.1007/978-3-642-40498-6_53
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Driver Task Load and Promoting Sociability through an Affective Intelligent Driving Agent (AIDA)

Abstract: Abstract. This work outlines the development of an Affective Intelligent Driving Agent (AIDA), a social robot that sits in a vehicle's dashboard and behaves as a friendly assistant. This highly expressive robot uses an Android smartphone as its face, which serves as the main computational unit for the system. AIDA determines what information may be relevant to the driver, delivers it at the most appropriate time, and resolves which expressions should be used when doing so. An evaluation was performed in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The characterization of the design space for socially interactive robots introduced in this work aims to facilitate a concrete discussion of past work, inform the selection and development of new robots for different applications, advise future experimental design, inspire novel applications, and help to improve the iterative design process of future robots, as the field of robotics continues to expand into new avenues of use. Ju and Sirkin, 2010;Kidd and Breazeal, 2004;Komatsu, 2010;Williams and Breazeal, 2013) Facial Affect SHORE (Costa et al, 2016), (Costa et al, 2016;Shahid et al, 2014;Williams and Breazeal, 2013; Elaine S. Short and Matarić, 2017) FACS Coding (Ekman and Friesen, 1975) Takeuchi et al (2006) Honda ASIMO Microsoft Peedy Tapus, Tapus & Mataric (2009) Bandit Virtual Bandit Vossen et al (2009) iCat Voice only Wainer et al (2006) Pioneer 2DX Virtual Pioneer 2DX Wainer et al (2007) Pioneer 2DX Virtual Pioneer 2DX Williams et al (2013) MIT AIDA AIDA on-screen App Wrobel et al (2013) Robulab Virtual Greta Zlotowski (2010) Nabaztag Virtual Nabaztag Table A.3: The results of the reviewed studies broken down by task performance differences and interaction performance differences. Lee et al (2015) N/A Yes N/A Yes Levy-Tzedek et al (2017) Task Performance Yes Leyzberg et al (2012) Task Performance Yes Li and Chignell (2011) Task Performance Yes Ligthart and Truong (2015) N/A Yes Lohan et al (2010) Task Performance, Interaction Performance No Looije et al (2012) Task Performance, Interaction Performance Yes Looije, Neerincx, & Cnossen (2010) N/A Yes Nomura (2009) Task Performance Yes Pan and Steed (2016) Task Performance, Interaction Performance Yes N/A Yes Powers et al (2007) Task Performance, Interaction Performance Yes …”
Section: Example: Grocer Store Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of the design space for socially interactive robots introduced in this work aims to facilitate a concrete discussion of past work, inform the selection and development of new robots for different applications, advise future experimental design, inspire novel applications, and help to improve the iterative design process of future robots, as the field of robotics continues to expand into new avenues of use. Ju and Sirkin, 2010;Kidd and Breazeal, 2004;Komatsu, 2010;Williams and Breazeal, 2013) Facial Affect SHORE (Costa et al, 2016), (Costa et al, 2016;Shahid et al, 2014;Williams and Breazeal, 2013; Elaine S. Short and Matarić, 2017) FACS Coding (Ekman and Friesen, 1975) Takeuchi et al (2006) Honda ASIMO Microsoft Peedy Tapus, Tapus & Mataric (2009) Bandit Virtual Bandit Vossen et al (2009) iCat Voice only Wainer et al (2006) Pioneer 2DX Virtual Pioneer 2DX Wainer et al (2007) Pioneer 2DX Virtual Pioneer 2DX Williams et al (2013) MIT AIDA AIDA on-screen App Wrobel et al (2013) Robulab Virtual Greta Zlotowski (2010) Nabaztag Virtual Nabaztag Table A.3: The results of the reviewed studies broken down by task performance differences and interaction performance differences. Lee et al (2015) N/A Yes N/A Yes Levy-Tzedek et al (2017) Task Performance Yes Leyzberg et al (2012) Task Performance Yes Li and Chignell (2011) Task Performance Yes Ligthart and Truong (2015) N/A Yes Lohan et al (2010) Task Performance, Interaction Performance No Looije et al (2012) Task Performance, Interaction Performance Yes Looije, Neerincx, & Cnossen (2010) N/A Yes Nomura (2009) Task Performance Yes Pan and Steed (2016) Task Performance, Interaction Performance Yes N/A Yes Powers et al (2007) Task Performance, Interaction Performance Yes …”
Section: Example: Grocer Store Robotmentioning
confidence: 99%
“…) Facial Affect SHORE , Shahid et al, 2014;Williams and Breazeal, 2013; Elaine S. Short and Matarić, 2017) FACS Coding (Ekman and Friesen, 1975)…”
mentioning
confidence: 99%
“…Furthermore, [2] showed that a robotic agent, used to help drivers with tasks such as managing phone and messages in a mock driving task, the robot agent helped reduce driver task load and promoted sociability better than a phone or a static agent.…”
Section: Related Workmentioning
confidence: 98%
“…Research for driving assistant robot has shown that an agent in the car can reduce the driver's task load and promote sociability for drivers [2], in tasks that relate to driving and managing incoming messages and phones. Considering many drivers have children in the back seat it is noteworthy that a different assistant may be designed for parent drivers.…”
Section: Introductionmentioning
confidence: 99%
“…Nomi can perform a number of functions, such as taking selfies for the occupants and controlling the vehicle's interface. In academia, researchers at MIT developed a social robot (AIDA) to reduce task load while driving and improve sociability with the user (Williams & Breazeal, 2013). The focus of these robots has been their engagement with the drivers and passengers of the cars.…”
Section: Introductionmentioning
confidence: 99%